TINJAUAN YURIDIS PASAL 4 AYAT 1 UNDANG UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN TERHADAP UPAYA MENDAPATKAN AKTA NIKAH - ISMAK SUBARDAN (GANEC SWARA, 2023)
The purpose of this research is to find out how the juridical review of article 4 paragraph (1) of law no. 1 of 1974 concerning Marriage regarding efforts to obtain a marriage certificate and to find out what causes marriage by married husbands without going through court approval. Marriages that often occur, namely when marriages are established between married men and women who are still virgins in secret or unregistered marriages, in other words polygamous marriages occur, of course this happens because the men do not want to deal with court proceedings which will complicate matters their marriage. Phenomena like this are very common in this modern era, meanwhile according to the Marriage Law No. 1 of 1974 Article 4 paragraph (1) requires that every husband who wants to be polygamous must obtain court approval to obtain a marriage certificate, this is not done by husbands for some reason. Many cases of polygamous marriages ignore the provisions stipulated in the Marriage Law, especially those contained in Article 4 Paragraph (1), so there is a legal review that must be put forward in addressing Article 4 Paragraph (1) so that there are not many polygamous marriages in series. namely by reviewing Article 4 Paragraph (1) that in order to obtain a Marriage Certificate it is not necessary to go through Court approval but can go directly to the Office of Religious Affairs in the area of residence for polygamous marriages to take place by attaching other supporting requirements that are already known by the Village Office local.